Binge Eating Disorder in obese patients suffering from psychosis and mood disorders - Fragiskos Gonidakis; Eirini Ralli; Evelyn Spilioti; Aimilia Tsertou; Maria Ginieri-Coccossis; Eleftheria Varsou (Archives of Depression and Anxiety - Peertechz Publications, 2017)
Purpose: The aim of the study was to investigate the possible impact of Binge Eating Disorder (BED) on quality of life (QoL),  social  anxiety, and perceived mental health in obese patients suffering from psychosis and mood disorder. Methods: Two hundred obese individuals suffering from psychosis and mood disorder who applied at a program for weight loss were approached during their first visit to the program. One hundred and ninety- six of the patients participated in the study.  Participants' weights  and  heights were measured prior to the administration of the questionnaires. Each participant completed the World Health Organization-Brief Quality of Life Assessment Scale, the  General Health Questionnaire, the Social Physique Anxiety  Scale, and a questionnaire on dietary and activity habits. Results:  Sixty-nine participants (35.2%) were found to suffer from BED according  to  DSM-V criteria. The comparison between the BED and non-BED participants showed that  the  Body  Mass Index (BMI) of the BED/psychosis  group  (mean:  35.4)  was  higher  (Mann-Whitney  U  test:  p=0.04)  than the non-BED/ psychosis group (mean: 31.8). Also the BED/mood disorders group showed lower than the non-BED/mood disorder scores in all the  QoL  measurements, general  health  (total  score  and  depression  sub-scale)  and social physique anxiety measurements. Furthermore, the psychological domain of OoL was the factor that differed  between  the  BED  and  non-BED  group  (OR=  9.8,  p=0.02)  indicating  thus  that  the  group  of  obese mental health patients that is suffering from BED is highly burdened with low psychological quality of life. Conclusion: BED in psychotic obese patients is related mainly with increased body weight  while in mood disorder obese patients is related with a variety of perceived aspects of well-being.